PENGEMBANGAN APLIKASI RECORD KEPATUHAN MENGKONSUMSI TEH ROSELLA TERHADAP PENURUNAN TEKANAN DARAH PADA PRA LANSIA DI KOTA BENGKULU - Linda, Linda; Nurhayati; Andeka Marleni, Wisuda; Ritawati; Ratnasari Dwi Putri, Novianthie (Politeknik Kesehatan Kemenkes Bengkulu, 2024)
Hypertension is the third cause of death (6.8%) in Indonesia after stroke (15.4%) and tuberculosis (7.5). The prevalence of hypertension at the age of 18 years and over based on measurement results is 31.7%, in women it is 31.9% and in men, it is 31.3%. In Bengkulu City, hypertension is a significant health problem. Based on data from research on hypertensive patients at Telaga Dewa Community Health Center in 2020, as many as 152 patients were recorded as suffering from hypertension in the period from January to March. One effort that can be made to reduce the incidence of hypertension is by consuming herbal medicines such as roselle tea which can reduce the increase in blood pressure. The research aims to control blood pressure in hypertensive patients by consuming rosella tea. Method: This research uses roaches, and qualitative qua approachesntitative. The results obtained were differences in systolic blood pressure before and after drinking rosella tea in the elderly in Benkulu City (p= 0.000), there is no difference in diastolic blood pressure before and after drinking rosella tea in the elderly in Benkulu City (p=0.683), there is a difference in the average knowledge before and after education using the compliance record application for consuming rosella tea to lower blood pressure (p=0,000).